Comparative efficacy of Vector Guard® to Olyset® Plus insecticide-treated nets against strongly pyrethroid-resistant Anopheles arabiensis in experimental huts in Tanzania - Machange, Jane Johnson; Mbuba, Emmanuel; Irish, Seth R.; Swai, Johnson Kyeba; Ntabaliba, Watson; Makungwa, Noely Otto; Ngonyani, Safina; Mpelepele, Ahmadi Bakari; Kibondo, Ummi Abdul; Odufuwa, Olukayode G.; Moore, Sarah Jane (Frontiers in Malaria, 2024)
IntroductionThe resistance of malaria vectors to pyrethroids has compromised the efficacy of pyrethroid insecticide-treated nets (ITNs). In response, ITNs with pyrethroids and piperonyl butoxide (PBO) synergists were developed to overcome metabolic pyrethroid resistance mechanisms. One such net is Vector Guard®. To demonstrate its potential efficacy for public health use, a comparative efficacy study was conducted to evaluate Vector Guard® relative to Olyset® Plus (a pyrethroid–PBO ITN proven to reduce malaria transmission more effectively than pyrethroid ITNs) and Royal® Sentry 2.0 (a pyrethroid-only ITN included to demonstrate the added benefit of PBO) in experimental huts in Tanzania.MethodsAn experimental hut trial using two blocks of a 7 × 7 Latin square design was conducted over seven rounds (49 experimental nights). Treatments were rotated at the end of each round, and volunteers were rotated nightly within one block. Both unwashed and 20× washed nets of each type were evaluated, alongside an untreated net used as a negative control. The primary endpoint was the proportion of Anopheles arabiensis that died within 24 h, and the secondary endpoint was the proportion of blood feeding. Data were analyzed using binomial logistic regression with fixed effects using a 7% non-inferiority margin.ResultsThe pooled results showed that Vector Guard® was non-inferior and was superior to Olyset® Plus, with higher mortality for Vector Guard® [28% vs. 18%; odds ratio (OR) = 1.93, 95%CI = 1.81–2.06]. Both pyrethroid–PBO nets were superior to Royal Sentry® 2.0 (p < 0.001) in terms of mosquito mortality. For the secondary blood feeding endpoint, Vector Guard® was also found to be non-inferior to Olyset® Plus (0.6% vs. 0.2%; OR = 2.37, 95%CI = 1.77–3.17). Vector Guard® showed similar efficacy to Royal Sentry® 2.0 in reducing the proportion of mosquito blood feeding (0.6% vs. 0.6%; OR = 0.85, 95%CI = 0.68–1.07, p = 0.161).ConclusionVector Guard® demonstrated superior mosquito mortality compared with both Olyset® Plus and Royal Sentry® 2.0, indicating that Vector Guard® is another promising pyrethroid–PBO ITN for the control of resistant malaria vectors. The addition of Vector Guard® to the class of pyrethroid–PBO ITNs will enable malaria control programs to select cost-effective ITNs, improving access to effective protection from malaria transmitted by resistant vectors.